Development of “Systemic Connections Between Oral Diseases and General Health” Course in the Curriculum of General Medical Practice Education: An Assessment of a Necessity Study - Seyed Hossein Tabatabaei; Saeede Nakhayi Nejad; Fatemeh Keshmiri (Journal of Medical Education and Development)
Introduction: Considering the impact of oral health on general body health, this study aimed to determine the necessity of designing an educational program titled "Oral Health and its Relationship with General Health" from the perspective of faculty members and educational experts in medical and dental faculties. Methods: In this descriptive-cross-sectional study, the target population of 378 individuals, including 278 medical faculty members, 69 dental faculty members, and 31 educational experts from the university's educational deputy, medical faculty, and dental faculty, completed a researcher-made, validated, and reliable questionnaire. Data analysis was performed using SPSS 22 statistical software and statistical tests such as t-test, ANOVA, and Pearson correlation coefficient. Results: The response rate was 66.6%, and 252 questionnaires were completed. 129 participants (51.2%) were male, and 123 (48.8%) were female. 87.7% of participants agreed on the necessity of developing and adding the discussed topic to the medical curriculum. 33.7% of participants agreed with providing education during the internship period, 47.2% with a duration of 4 weeks, 81% with the course being taught by oral and maxillofacial disease specialists, and 50.6% with this education being provided in the dental school's clinical departments. Conclusion: From the perspective of most participants, developing the mentioned course in the general medical education curriculum is essential. Therefore, it is suggested that the course be considered by relevant planners when revising medical internship educational programs.